A Simple Pipe-Drag Sweeping Device - Suzuki, Ryokichi (The International Hydrographic Review, 2015)
It is very difficult to judge on echograms whether a doubtful echo is a real obstruction or merely electronic noise. The author has designed a pipe-drag sweeping device to examine doubtful echoes and made several trials with it. The first trial was carried out in August 1967 in Ube Passage off Ube, Yamaguchi Prefecture, and then others later in Chiba Harbour (November 1968), Yokohama (December 1968 and January 1970) and Negishi (February 1970).